The Interaction Effect of Personality Traits and Gender Differences on Risky Behaviours among First-Year University Students in South Africa - Choja Oduaran; Samson Agberotimi; Samuel Moetji (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2022)
This article investigates the effect of personality traits and gender differences on risky behaviours among first-year students of a South African university. A sample of three hundred and twelve (312) first-year students comprising 59.6 per cent females was selected as participants. Data were collected with a questionnaire to measure risky behaviours, personality traits, and demographic information. Collected data were subjected to statistical analysis using the statistical package for social sciences v23. Descriptive and inferential statistics were conducted. Results showed that the use of alcohol to the extent of being drunk, staying out late at night without parents’ knowledge, taking chances while doing hobbies, reckless driving, and unsafe sexual practices are prominent among the students. Agreeableness (F (1, 308) = 9.863, p <.005), and conscientiousness (F (1, 307) = 20.445, p <.001) personality traits significantly influenced risky behaviours, while there was a significant gender difference (t (310) = 6.13, p <.01) in the rate of risky behaviours among the participants. It is concluded that personality traits significantly contribute to risky behaviours. In addition, males are generally more inclined to engage in risky behaviours than females. Intervention-based research and activities to address the issue of risky behaviours among students are recommended. This study contributes to the study of risky behaviour among young persons with a reference to the context of university life in South Africa by considering gender as an important factor that contributes to risky behaviours among first-year university students.